UPAYA KOMUNITAS SOHIB LITERASI INDONESIA (SOLID) DALAM MENINGKATKAN MINAT BACA ANAK - Ari Pamungkas (Program Studi PGSD Universitas Flores, 2023)
Reading interest still a polemic that has not been resolved until now. Considering this problem requires support from various parties to be able to increase children's reading interest such as parents, educational institutions and the community environment itself. This research aims to find out the efforts of the Indonesian Literacy Sohib Community in increasing the reading interest of children. This research uses a qualitative approach with descriptive types of research. Data collection methods used are observation, interview and documentation. The subjects in this study were eleven informants consisting of one community leader, 5 children in active activities, and 5 mothers of children. The results of the research show that the community not only strives to provide information sources such as places to provide information sources such as books, children's magazines, comics, novels and as a link between information sources and knowledge with users to increase their reading interest but also as teachers for children who are still unable to read, train more positive children's social The benefits of the presence of this community are not only felt by direct children but also parents. Parents find it helpful to the presence of this community such as the ability to read it develop and decrease negative behavior.